Mainstream capnography system for nonintubated children in the postanesthesia care unit: Performance with changing flow rates, and a comparison to side stream capnography. Issue 12 (24th September 2016) - Nagoshi, Makoto; Morzov, Rica; Hotz, Justin; Belson, Paula; Matar, Marla; Ross, Patrick; Wetzel, Randall
Abstract: Introduction: Monitoring of exhaled carbon dioxide (CO2 ) in nonintubated patients is challenging. We compared the precision of a mainstream mask capnography to side stream sampling nasal cannula capnography. In addition, we compared the effect of gas flow rates on the measured exhaled CO2 between mainstream mask and side stream nasal cannula capnography. Methods: A mainstream mask capnography system (cap‐ONE) was tested. Children (weight of 7–40 kg, ASA 1–2) following anesthesia for minor procedures were assigned randomly to side stream or mainstream sampling groups. The side stream group wore a nasal cannula with CO2 side port (NC). In the postanesthesia care unit, O2 flow was started at 5 l·min −1, reduced to 2 and then 0.25 l·min −1 every 3 min. Capnogram analysis measuring heights of all the waveforms was performed for continuous 120 s from the end of recording at each O2 flow rate for each group. Results: Fifty‐eight children were enrolled and 39 were analyzed (18 side stream NC and 21 mainstream mask). There were two mouth breathing children excluded from study in side stream NC group due to failure to capture measurable CO2 waveforms. Peak CO2 values measured by mainstream mask system were normally (Gaussian) distributed with smaller standard deviation (sd ) at each O2 flow than were those measured by side stream NC system which demonstrated irregular distributions with largersd . Peak CO2 values measurement was less affected by a change in flow rate in mainstream mask group than in side stream NC group ( P = 0.04 in 5–0.25 l·min −1 O2 flow change). Conclusion: A new mainstream mask system (cap‐ONE) performed with greater precision than side stream NC monitoring regardless of mouth breathing. Measurement of peak CO2 values by mainstream mask system showed normal distribution with smaller standard deviation (sd ) and was less affected by O2 flow change in predictable fashion. Abstract :